2017
DOI: 10.7759/cureus.1877
|View full text |Cite
|
Sign up to set email alerts
|

Burnout of Physicians Working in Primary Health Care Centers under Ministry of Health Jeddah, Saudi Arabia

Abstract: IntroductionThe levels of physicians' job satisfaction and burnout directly affect their professionalism, punctuality, absenteeism, and ultimately, patients' care. Despite its crucial importance, little is known about professional burnout of the physicians in Saudi Arabia. The objectives of this research are two-fold: (1) To assess the prevalence of burnout in physicians working in primary health care centers under Ministry of Health; and (2) to find the modifiable factors which can decrease the burnout ratio.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 30 publications
1
43
1
Order By: Relevance
“…Overcrowding is also a major contributor toward physicians' burnout [17]. Bawakid et al [17,29] showed a positive correlation between the number of patients per day and physicians' burnout. Similarly, general cleanliness of the hospital or a health care center is also recognized as a positive predictor not only for the patients' satisfaction, but also as it affects the staff working in it [17].…”
Section: Discussionmentioning
confidence: 99%
“…Overcrowding is also a major contributor toward physicians' burnout [17]. Bawakid et al [17,29] showed a positive correlation between the number of patients per day and physicians' burnout. Similarly, general cleanliness of the hospital or a health care center is also recognized as a positive predictor not only for the patients' satisfaction, but also as it affects the staff working in it [17].…”
Section: Discussionmentioning
confidence: 99%
“…This extra administrative workload leads to physician's burnout. [ 16 ] However, teaching/training postgraduate trainees was one area where around 60% of FPs showed interest. Similar findings were reported in the studies conducted in Canada[ 26 ] and Japan.…”
Section: Discussionmentioning
confidence: 99%
“…[ 15 ] However, recent studies have highlighted high level of job dissatisfaction and stress among doctors affecting quality of care. [ 16 17 ] Around 38% Canadian doctors described “medical practice” itself as extremely stressful, as one has to deal with difficult cases, aggressive patients, and their attendants. [ 18 ] Modern changes in the healthcare system, increase in the workload, reduced physician's autonomy, and respect are some of the main reasons for dissatisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…The aMBI is a reliable and highly validated tool that has been used to measure burnout in doctors and other healthcare professionals. [15][16][17][18][19][20][21] To assess burnout, there were nine questions from the aMBI, and three additional questions concerning satisfaction with medicine. 19 Questions were scored on a seven-point scale, ranging from never (0) to every day (6).…”
Section: Comparisons Between Groupsmentioning
confidence: 99%